Complications of platysma myocutaneous flap in patients with oral submucosal fibrosis: A systematic review - Uma Shanker Pal; Harshita Maurya; Roop Ganguly; R.K. Singh; Vijay Kumar (Journal of Oral Biology and Craniofacial Research)
Objective: This systematic review aims for the explanation of possible postoperative complications, efficacy and limitations of Platysma myocutaneous flap (PMF) in patients with oral submucosal fibrosis (OSMF). Method: An electronic search of the literature was undertaken using PubMed, Cochrane Library, clinical trials.gov in the year 2021, using MeSH terms and keywords to identify prospective, retrospective and observational studies, controlled trials as well as case reports over the period 1913 to December 2021, addressing the patients with a mouth opening <25 mm and habit of gutkha chewing. PMFs are used as a form of intervention. Patient follow up period should be mentioned. Results: A total of 5 publications were included. 2 were prospective studies and 3 were case reports with 79 subjects between the ages of 18 and 45. All included studies reported complications in a non-significant way (p-value = 0.870) with positive results as they impact the patient's functional outcome (mouth opening) in a statistically significant manner (p < 0.0001 and 95% CI) with good patient compliance. Conclusion: PMF is rarely used in routine practice due to their technical difficulty and potential complications like venous congestion and necrosis. In this systematic review, the authors provide valuable insight into the causes of complications and the efficacy of PMFs in OSMF patients. In the process of platysma flap harvesting, it is especially important to preserve the skin flap, arterial perforators and arteries, veins in supra and sub-platysmal flap elevation. Aside from proper flap placement and tunnelling, postoperative care is equally important.